The Use of Trainer Kits to Improve Learning Outcomes of Electrical Lighting Installation - Koloway, Julius; Kattie, Christine (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
Learning outcomes are mental processes that lead to mastery of knowledge skills habits or attitudes that are acquired stored and implemented by causing permanent behavior Therefore to improve student learning outcomes using the Class Action Research CAR method the Kemis and McTaggart model design uses a spiral system that includes several cycles Each cycle consists of the following stages: i Planning ii Implementation and Observation and iii Reflection The Classroom Action Research method results show that teachers can use the trainer kit as a learning medium and operate it according to the time that has been arranged Some influential students who become more knowledgeable in studying Electrical Lighting Installation materials using a trainer kit have also improved learning outcomes Some already know and understand and can even practice it well because students need guidance from subject teachers and facilities from majors and schools for better practice Through learning with home lighting installation trainers in electrical lighting installations students can improve learning outcomes for class XI SMK Negeri 2 Manado in the 2021 2022 academic year in the sub competence of installing and connecting installation systems < strong>< p>